Synchro-Mining: the New Sight - Amosha, O.; Cherevatskyi, D.; Pivnyak, G.; Shashenko, O.; Borodai, L. (Економічний вісник Донбасу, 2019)
The analysis of Synchro-Mining alternatives, performed by the paper, has shown the multidimensionality being typical for the ideology and even controversy stipulating complexity of its understanding both by practices and by qualified scientists. It has been substantiated that it is expedient to base the Synchro-Mining phenomenon on Mining interpretation by Merriam-Webster Dictionary version relying upon the existence primacy of a mining enterprise (i.e. a mine, quarry, open pit, well etc.): Mining exists irrespective of the mineral extraction until the enterprise is liquidated physically. Thus, Synchro-Mining is diversification of the key activity of a mining enterprise performed in parallel with Mining whether it is coal or ore preparation, generation of electric energy and thermal energy, early Post-Mining measures, commercial extraction of methane, deep treatment of mine water, progress of circular economy etc. not only in the form of vertical integration of various businesses (i.e. hierarchical production method) but also in the form of heterarchies (i.e. network capitalism) or in the form of industrial parks.